Women Empowerment Inequality at the Ministry of Religion - Cian Ibnu Sina (UIN Sunan Gunung Djati Bandung, 2020)
The purpose of this paper is to describe a gender-based human development profile in the religious field. This study uses Secondary Data Analysis, namely the Ministry of Religion in 2016 Figures. The findings show that the achievement of women's involvement in the Ministry of Religion is still far from balanced, there are still gaps. Only 33.67% of women occupying the positions of secretary general, directorate general of Islamic education and community service, only 34.41 percent of UIN state employees in Indonesia, 35.37% of R&D & religious staff, 40.68 percent of religious educators, and non-civil servants of religious educators. 32.31%, hafidzah 60.95%, board of judges 17.61%, mufassirah 19.75%, writer 20.51%, researcher 24.32%. The strategic position is still dominated by men, the highest number of women is in the hafidzah position (memorizing the Qur'an), while other positions that are far more strategic are still below 50%. This indicates that development in the field of religion even though women are still neglected, is not yet gender responsive.